Psychophysiological stress: a significant parameter in drug pharmacokinetics. (October 2013) - Konstandi, Maria
<x xml:space="preserve">Abstract</x> Introduction: The available evidence suggests that psychophysiological stress regulates a substantial number of factors, which in turn, can alter the pharmacokinetic parameters of a drug. Areas covered: Due to the multi-factorial involvement of stress in the regulation of a drug's pharmacokinetic profile, this review has been limited to and focuses only on the impact of stress on drug metabolism. Specifically, the review presents studies which have indicated that psychophysiological stress can significantly modify the function of the major hepatic drug-metabolizing enzymes belonging to cytochrome P450s (CYP) family in a stress-specific and species-specific manner. Furthermore, the article discusses how stress related changes in CYP regulation appear to be mediated by glucocorticoids and epinephrine/norepinephrine. This can lead to an increased rate of metabolism of the majority of prescribed drugs and chemical pre-carcinogens. Expert opinion: Apparently, psychophysiological stress has a significant impact on some of the major drug-metabolizing enzyme systems. Therefore, stress should be considered as an important factor affecting drug metabolism and pharmacokinetics, with the potential to significantly alter the outcome of drug therapy and toxicity. Despite the fact that the majority of data come from experimental studies, it is conceivable that the elimination of stress is an essential condition in order to ensure the optimal outcome of pharmacotherapy.